2016
DOI: 10.4081/monaldi.2006.585
|View full text |Cite
|
Sign up to set email alerts
|

Dose dependence of efficacy and safety of subcutaneous immunotherapy

Abstract: A number of experimental and clinical evidence has shown that exposure to high amounts of allergen molecules favours the development of tolerance. This is true also for subcutaneous immunotherapy (SCIT), for which a dose dependence of clinical efficacy was clearly demonstrated. The effective doses, measured as μg of major allergens, to be administered during maintenance treatment were established for the main allergens. Regarding pollens, the range of effectiveness corresponds to 25-41 and 13-20 μg of major al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These two aspects are obviously related to each other, because patients with adverse reactions to SIT are unlikely to have the same clinical benefit as those who tolerate the treatment. In fact, the cumulative dose received will inevitably be lower, and the concept of dose dependence regarding the effectiveness of SIT is not up for discussion 90. A randomized, double-blind, placebo-controlled study of 248 patients treated with perennial allergens (house dust mite, cat and dog epithelium) confirmed these observations, showing that treatment with omalizumab was associated with significantly fewer asthmatic and systemic adverse reactions compared with placebo, and enabled achievement of the usual maintenance dose 91.…”
Section: Combination Of Omalizumab and Sitmentioning
confidence: 99%
“…These two aspects are obviously related to each other, because patients with adverse reactions to SIT are unlikely to have the same clinical benefit as those who tolerate the treatment. In fact, the cumulative dose received will inevitably be lower, and the concept of dose dependence regarding the effectiveness of SIT is not up for discussion 90. A randomized, double-blind, placebo-controlled study of 248 patients treated with perennial allergens (house dust mite, cat and dog epithelium) confirmed these observations, showing that treatment with omalizumab was associated with significantly fewer asthmatic and systemic adverse reactions compared with placebo, and enabled achievement of the usual maintenance dose 91.…”
Section: Combination Of Omalizumab and Sitmentioning
confidence: 99%
“…At the onset of the TAKE‐AWAY trial, peanut OIT trials reported maintenance doses ranging from 125 to 4000 mg peanut protein, with no adverse events (AEs) requiring epinephrine reported during a biweekly step‐up protocol to 4000 mg peanut protein . A high maintenance dose confers an increased likelihood of SU in subcutaneous immunotherapy (SCIT) trials for inhalant and venom allergies, while this issue has not been adequately addressed for OIT. However, in a recent peanut OIT study, maintenance dose was not decisive for SU 4 weeks after cessation of OIT.…”
Section: Introductionmentioning
confidence: 99%
“…Its evidence of effectiveness was increasingly apparent with the improvement of quality of allergen extracts, but the concern of adverse reactions, that were rarely life-threatening and sometimes fatal, emerged as a drawback. In fact, SCIT is clearly dose-dependent according to both efficacy and safety, and the cutoffs of doses associated to an increased risk of reactions were identified and measured in microgram of major allergens [13]. The development of non-injective routes of AIT was driven by the safety issue, and the need was met by SLIT, which showed a good clinical efficacy while maintaining a suitable safety, with doses hundreds of times higher than those used for SCIT [14].…”
Section: Expert Opinionmentioning
confidence: 99%